Corporate Social Responsibility Disclosure: The Comparative Study Between Islamic Banking in Indonesia, Malaysia and Singapore - ., Meldona; ., Segaf; Al Idrus, Salim (International Journal of Engineering and Technology, 2019)
Background: The concept of Corporate Social Responsibility (CSR), that has closely related with the concept of sustainable development and social economy, has appeared as a trend in Islamic banking sector. Objectives: This researchâ€™s aim is to compare the CSR Disclosure of Islamic Banks (IBs) in Indonesia, Singapore and Malaysia by using a model of Islamic Social Reporting Index (ISR Index). Method: The methodology of this research is comparing the data by using method of content analysis. This research used 7 Islamic Banks as the sample, which is 3 Indonesian Banks, 1 Singaporean Bank, and 3 Malaysian Banks, which has been chosen purposively based on the criterias that those banks were local banks, have biggest and medium asset value, and performed fit financial reports to research period at 2010-2014. Findings: The ISR index showed that there were increasing implementation of social responsibility for all Islamic Banks in the three countries from year to year for all disclosure theme, but still need to increase their attention on Environment theme which is Endangered Wildlife, Conservation of Environment, Environmental Education, Environmental Pollution, Environmental Audit and Environmental Management System, Environmental Product or Process Related. The theme characteristics of CSR Disclosure from three countries shows that Indonesian Islamic Bank prefers to Employer and Environment Theme, The Singaporean Islamic Bank prefer to Product and Service Theme, meanwhile Malaysian Islamic Bank prefer to finance and investment theme and Society Theme. The further research should be garner the more objective data especially for The Singaporean Islamic Bank since the Islamic Banks used in this research is a joint venture with Commercial Banks as base of data. Keywords: CSR Disclosure, ISR Index, Islamic Bank.Â Â